Comparative Study of Electricity Spot Price Volatility Dynamics and Hedging Effectiveness of Electricity Futures - International Comparison (Europe - Asia Pacific) - Wang, Yuelang (2017)
The openness of deregulation and access to the privatization in power transmission networks created the electricity exchange various level of liquidity and maturity in trading markets. The late establishment and immature system in Asia-pacific regions needs more patience and explorations for power marketers to deal with the unforeseeable vagaries in selling futures and forwards contracts in spot markets.In this study, the hedging strategies effectiveness has been explored in Europe (United Kingdom, Germany and France) and in Asia Pacific (Australia). It should note that Germany, France and UK have the most liquid Electricity Spot and Futures and in Asia Pacific, the most liquid market Electricity markets remains in Australia. Singapore Futures market only opened in 2014, Japan and Korea Electricity Futures are at a study stage. By applying the approaches like naïve, OLS and CCGARCH for the given base- and peak- load daily data of monthly futures contracts, we find that under the conventional variance reduction measurement, peak-load futures hedging performance has been improved than base-load futures of both OLS and CCGARCH; whilst under Value at Risk (VaR) measurement, both contracts share the similar results in risk reductions. Besides, there indicates poor correlation between all spot and futures in four markets. The instability of electricity co-movements may imply a lot of limitations on exploiting potential merits of electricity futures for all market participants. The volatile movements in the contemporaneous relations of spot and futures may emphasize deficiency in assumptions of short-run relationships in both markets, which may hinder to achieve objective of active profitable trading.